INTERNALISASI NILAI SPORTIVITAS MELALUI PEMBELAJARAN PENDIDIKAN JASMANI DI SEKOLAH DASAR NEGERI: Studi di Sekolah Dasar Negeri Loktabat 1 Banjarbaru - Arifin, Syamsul (2013)
The dissertation contains research results on internalization of sportsmanship values through physical education teaching-learning in State Elementary SchoolLoktabat 1, Banjarbaru. The research involved teachers and students conducting physical education teaching-learning. The main issue of the study is: How is the process of internalizing the values of sportsmanship through physical education in an elementary school? The theory employed as the foundation of the research was Bandura's social learning theory. The main issue is elaborated into the following research questions: (1) How do physical education teachers develop lesson plans that internalize sportsmanship?; (2) How is the process of cultivating the sportsmanship values of knowing, training, and being in the teaching-learning of physical education?; (3) How do teachers evaluate and improve the teaching-learning that internalize sportsmanship values?; (4) What factors encourage and inhibit the process of internalizing sportsmanship values?; (5) What factors encourage and inhibit the process of evaluating students' sportsmanship? To obtain data, qualitative approach using observation, interview, and documentation was employed. The data were then analyzed using Miles' andHuberman's model (1992) through the stages of data collection, data reduction, data display, and inference. The results of data analysis are as follows: (1) The physical education teachers have developed lesson plans, which beginwith the writing of lesson plansand later ontheir implementation in the field, but the writing was still done by adapting another lesson plan, especially in terms of value development planning;(2) The process of internalizing sportsmanship values among students were conducted following the stages of objective formulation, materials, method, resources, and evaluation, and then implementation in the teaching and learning of theories and field practice; (3) The results of the internalization of sportsmanship values among students were continuously evaluated directly by physical education teachers during the teaching-learning process; (4) The availability of facilities and equipment for physical education teaching-learning has become the factor that encourage the success of cultivating sportsmanship values among students; however, the teachers' low ability in using a value-based teaching-learning model has become the obstacle for developing sportsmanship; (5) The physical education teachers had been used to assessing students' sports practice in the field without understanding and using appropriate and accurate evaluation tool for sportsmanship values, so that they did not pay much attention to the changes in students' attitudes and characters. Generally, the guidance of sportsmanship through Physical Education in elementary schools is emphasized more on the levels of training and being than knowing. Disertasi ini berisi hasil penelitian tentang internalisasi nilai sportivititas melalui pembelajaran pendidikan jasmani yang dilakukan di Sekolah Dasar Negeri Loktabat 1 Banjarbaru. Penelitian ini melibatkan guru dan siswa yang telah melaksanakan proses pembelajaran pendidikan jasmani. Masalah pokok yang menjadi kajian disertasi ini adalah bagaimana proses internalisasi nilai sportivitas melalui pendidikan jasamani di Sekolah Dasar?.Adapun teori yang digunakan sebagai landasan penelitian adalah teori social learning dari Bandura. Secara rinci masalah pokok penelitian dijabarkan kedalam pertanyaan penelitian sebagai berikut: (1) Bagaimana guru pendidikan jasmani mengembangkan rencana pembelajaran internalisasi sportivitas?; (2) Bagaimana proses penanaman knowing, training, dan being nilai sportivitas dalam pembelajaran pendidikan jasmani?; (3) Bagaimana guru mengevaluasi dan memperbaiki proses pembelajaran internalisasi nilai sportivitas?; (4) Faktor apa saja yang menjadi pendorong dan penghambat proses internalisasi nilai sportivitas?; (5) Faktor apa saja yang menjadi pendorong dan penghambat proses evaluasi sportivitas siswa? Untuk menghasilkan data penelitian menggunakan pendekatan kualitatif dengan tehnik observasi, wawancara dan dokumentasi. Data dianalisis menggunakan model Miles dan Huberman (1992) melalui tahapan pengumpulan data, reduksi data, display data, dan penarikan kesimpulan. Hasil analisis data adalah sebagai berikut : (1) guru Pendidikan Jasmani telah mengembangkan rencana pembelajaran yang diawali dengan penyusunan rencana pembelajaran (RPP) untuk dilaksanakan di lapangan namun RPP tersebut masih bersifat adopsi dari bentuk RPP lain terutama dalam perencanaan pengembangan nilai; (2) proses menginternalisasikan nilai sportivitas pada peserta didik dilakukan sejak menyusun tujuan, materi, metode, sumber dan evaluasi serta dilaksanakan dalam pembelajaran teori dan praktik di lapangan; (3) hasil internalisasi nilai sportivitas oleh peserta didik dievaluasi secara terus menerus secara langsung oleh guru Pendidikan Jasmani selama proses pembelajaran; (4) tersedianya fasilitas dan alat pembelajaran pendidikan jasmani di sekolah dasar, menjadi faktor pendorong keberhasilan penanaman nilai sportivitas pada peserta didik, namun rendahnya kemampuan guru dalam menggunakan model pembelajaran yang berbasis nilai menjadi kendala pengembangan sportivitas tersebut; (5) guru-guru pendidikan jasmani telah terbiasa menilai praktik olahraga siswa di lapangan, akan tetapi tidak memahami dan tidak menggunakan alat evaluasi yang baik dan tepat untuk menilai sportivitas, sehingga kurang memperhatikan perubahan sikap dan karakter siswa. Secara umum pembinaan sportivitas melalui Pendidikan Jasmani di Sekolah Dasar lebih banyak ditekankan pada training dan being dari pada tataran knowing.